SMART OPERATIONS: IMPLEMENTING AI-DRIVEN TECHNOLOGIES FOR ENHANCED EFFICIENCY IN SUPPLY CHAIN MANAGEMENT - Fauziah, Luluk; Suharyanto, Suharyanto; Herlina, R. Lisye; Sutisna, Adang; Gymnastiar, Iman Ahmad (Branding: Jurnal Manajemen dan Bisnis, 2024)
Supply chain management is a vital element in a company's overall operations, but is faced with complex challenges such as fluctuations in market demand, logistical complexity, resource limitations, and the risk of disruption. This research aims to explore the role of artificial intelligence (AI)-based technology in overcoming these challenges. This research will be carried out using a qualitative approach, collecting data from various relevant sources and then analyzing it systematically. Through this approach, this research aims to gain a deep understanding of the long-term impact of applying AI to the supply chain, including improving operational efficiency, competitive advantage, supporting sustainability, and the evolution of the human role. The research results show that AI makes a significant contribution to improving companies' operational efficiency, providing competitive advantage through enhanced responsiveness, supporting more sustainable business practices, and enabling the evolution of the role of humans in the supply chain. The practical implication of this research is that the application of AI technology can help companies achieve better performance and prepare for future challenges in an increasingly complex and dynamic business environment.